A case report on eumycetoma: An uncommon disease in the suburban areas of Maharashtra - Shah, Bimal Chandrakant; Puthenpurayil, Susanna Jose; Singh, Divyanshu Akhilesh (Indian Journal of Case Reports, 2024)
Mycetoma is an uncommon chronic granulomatous infection of cutaneous and subcutaneous tissues. The causal agents are soil saprophytes with around 33 species identified, namely bacteria or fungi. The World Health Organization categorized mycetoma as a neglected tropical disease. In India, the southern states have a high prevalence. Our case report presents the case of a 37-year-old male patient who presented to the hospital for diagnosis and treatment of foot swelling in his right foot region. Initially, the cause of the lesion was unknown. After radiology and laboratory investigations, the case was diagnosed with Mycotic Mycetoma or Eumycetoma. Although this study reports a single case, the findings might expand our understanding of mycetoma and its prevalence, even in the uncommon suburban regions of Maharashtra. Reporting neglected tropical diseases can alert healthcare about their spread and global burden, even in uncommon areas.